Antimicrobial Guided Phytochemical Evaluation of the Pods of Caesalpinia pulcherrima - Sudhakar, M.; Krishnaiah, P.; Rao, A.L.; Raju, D.B. (Asian Journal of Chemistry, 2016)
The alcoholic extract of the pods of the plant C. pulcherrima afforded five antimicrobial compounds: four homoisoflavonids (4-O-methylsappanol, protosappanin A, brazilin and caesalpin J) and ethyl 2,4,6-trihydroxy benzoate. The structures of the compounds were established by means of NMR spectroscopic analysis. Antimicrobial activity of the compounds was evaluated against pathogenic gram –ve and gram +ve bacteria and fungi.